Variation in Symmetry Around Doped Pr(III) ion in Saturated Solution of Biologically Important Ligands - Jain, Samata; Jain, Sushma (Asian Journal of Chemistry, 2011)
The absorption spectra of doped Pr(III) ion with some biologically important ligands (viz. indole acetic acid, indole-3-butyric acid, gibberalic acid, ascorbic acid and pyridoxine) have been studied in aqueous and organic solvents (DMSO, DMF, EtOH, H2O). The doped model involves small concentration of Pr(III) ion salt (0.0435 g) in saturated solution of ligand in various solvent at 298 K. The electronic spectral parameters viz. Judd-Ofelt (Tl), Racah parameter (Ek), Slater-Condon parameter (Fk), Lande parameter (z4F), bonding parameters (b1/2), naphelauxetic ratio (b), covalency (%) (d), rms deviation (s) and Peacock constant (K) have been evaluated. The study infers the change in symmetry around doped Pr(III) ion and metal-ligand interaction. The greater change in symmetry observed when DMSO is taken as solvent in study. The Peacock proportionality constant (K) has been found to constant in almost all systems under study.